Determination of the Thermal Diffusivity of Plasmonic Nanofluids Containing PVP-Coated Ag Nanoparticles Using Mode-Mismatched Dual-Beam Thermal Lens Technique - C. S. Lopes; V. M. Lenart; R. F. Turchiello; S. L. Gómez (Advances in Condensed Matter Physics)
Plasmonic nanofluids have found applications in many fields, for example, coolants, solar collectors, and theranostics agents. For such applications, an important parameter is the thermal diffusivity. In this communication, we present an experimental study concerning the dependence of the thermal diffusivity of highly diluted aqueous plasmonic nanofluids containing PVP-coated silver nanoparticles on the concentration. Measurements were made by employing the time resolved mode-mismatched thermal lens technique and the results show an enhancement of the thermal diffusivity, when compared to that of the carrier fluid, on increasing the number density of the nanoparticles and being rather constant as a function of the power of the pump beam.